The first snap-fit handbook : creating and managing attachments for plastic parts - Bonenberger, Paul R. (Hanser ; Hanser Gardner Publications, 2005)
"This book organizes and presents all design aspects of snap-fits with an emphasis on the systems level thinking required to create world-class attachments. Beginning as well as experienced product designers will find the information they need to develop snap-fits more efficiently and avoid many common snap-fit problems. A new chapter in this edition discusses issues associated with managing snap-fit technology in an engineering organization. Suggestions for introducing the technology and strategies for ensuring long-term snap-fit technical capability and learning are provided."--Jacket